Pengaruh Pembiayaan Murabahah, Musyarakah, dan Mudharabah terhadap ROE dengan ROA Sebagai Variabel Intervening pada Bank Syariah Indonesia Periode 2019-2022 - Diyah Ayu Wulandari; Ali Mauludi AC (J-MAS (Jurnal Manajemen dan Sains), 2023)
Return On Equity (ROE) is a measure to see the performance of Islamic banks in terms of profitability. This study uses ROA as an intervening variable because ROA is an indicator of a bank's ability to earn returns on a number of assets it owns. Likewise, ROA measures the level of profit on the assets used to generate that profit. Factors that affect ROE in this study are murabahah, musyarakah, and mudharabah financing. This research is a quantitative research using secondary data, namely the annual data of Indonesian Sharia Banks published on the OJK website studied for the 2019-2022 period. The method used in this research is multiple linear regression with a significance level of 0.05 and path analysis. The results showed that partially the financing of Murabahah, Musyarakah, Mudhrabaha, and ROA has a significant effect on ROE. Partially, Murabahah and Musyarakah financing does not have a significant effect on ROA, while Mudharabah financing has a significant effect on ROA. Partially Musyarakah and ROA financing have a significant effect on ROE, while Murabahah and Mudharabah financing have no significant effect on ROE. Return On Assets (ROA) can mediate murabahah, musyarakah and mudharabah financing for Return On Equity (ROE) at Bank Syariah Indonesia for the 2019-2022 period.